Explore IDNLearn.com to discover insightful answers from experts and enthusiasts alike. Get accurate and comprehensive answers to your questions from our community of knowledgeable professionals.

What is the solution to this equation?

[tex]\[ 3(n-9)-2(n+4)=6n \][/tex]

[tex]\( n = \square \)[/tex]


Sagot :

Let's solve the equation step-by-step.

Given:
[tex]\[ 3(n-9) - 2(n+4) = 6n \][/tex]

1. Distribute the constants inside the parentheses:
[tex]\[ 3n - 27 - 2n - 8 = 6n \][/tex]

2. Combine like terms on the left side:
[tex]\[ (3n - 2n) - 27 - 8 = 6n \][/tex]
[tex]\[ n - 35 = 6n \][/tex]

3. Isolate the variable [tex]\( n \)[/tex] by moving the [tex]\( n \)[/tex] term to the right side:
[tex]\[ -35 = 6n - n \][/tex]
[tex]\[ -35 = 5n \][/tex]

4. Solve for [tex]\( n \)[/tex] by dividing both sides by 5:
[tex]\[ n = \frac{-35}{5} \][/tex]
[tex]\[ n = -7 \][/tex]

So, the solution to the equation is:
[tex]\[ n = -7 \][/tex]
We are delighted to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. IDNLearn.com is your go-to source for dependable answers. Thank you for visiting, and we hope to assist you again.